Determinants of Profit Growth Based on Financial Ratios at PT Ace Hardware Tbk - Ivan Putranto; Citra Eliyani (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2022)
This purpose of the study was to determine the effect of current ratio (CR), Debt to equity ratio (DER), Return on Equity (ROE), Total Asset Turn Over (TATO) on provit growth at PT Ace Hardware Tbk for 2010-2021 period by partially or simultaneously. The method used in this study is a descriptive method using a quantitative approach. The data used in this study is secondary data in the form of financial statements at PT Ace Hardware Tbk for 2010-2021 period. Data processing by used SPSS version 25 program. Data analysis used classical asumption test, linier regression test, hypothesis test by T test and F test, and determination test. Based on the results of the classical assumption test, the data is normally distributed, there is no multicollinearity problem, there is no heteroscedasticity problem and free from autocorrelation. Partially, the current ratio variable has no effect on profit growth (0,223>0,05). Debt to equity ratio has an effect on profit growth (0,014<0,05), return on equity has no effect on profit growth (0,141>0,05). Total assets turn over has no effect on profit growth (0,353> 0,05). Simultaneously, the variables current ratio, debt to equity ratio, return on equity, and total assets turnover have an effect on profit growth of 0,021<0,05. The value of the coefficient of determination (R2) obtained from results of this study was 77,2% while the remaining 22,8% was influenced by other variables have not researched.